Seasonal zooplankton development in a temperate semi-enclosed basin: two years with different spring bloom timing. (8th January 2018) - Mahara, Natalie; Pakhomov, Evgeny A; Jackson, Jennifer M; Hunt, Brian Pv
Abstract: Coastal temperate waters undergo considerable intra- and interannual environmental variations, which is reflected in the dynamic nature of their zooplankton communities. Since zooplankton phenology is dependent on several factors, particularly temperature and spring bloom timing, it is imperative to understand how zooplankton communities may shift under future climate conditions with warmer temperatures and more variable spring bloom initiation. To examine zooplankton phenology and response to shifts in bloom timing, we analyzed fortnightly zooplankton and environmental samples collected in the northern Strait of Georgia (B.C., Canada), a large semi-enclosed temperate basin, in 2015 and 2016. Despite a 5-week difference in spring bloom timing, zooplankton community succession was remarkably similar between years. In both years, biomass peaked within the same calendar week and communities were separated into winter, early spring and summer-autumn assemblages that formed independent of the spring bloom timing. Although some species-level phenological differences were observed between years, predominately delayed population development, zooplankton communities appeared to demonstrate resilience to interannual environmental variations on the whole. If ongoing warming shifts the timing of zooplankton consumers' life history timing, it could lead to a mismatch with their zooplankton prey resource that exhibits comparatively less interannual variability.